Rural and urban women entrepreneurssa comparison of service needs and delivery methods priorities - Angela Davis (International Journal of Business Science & Applied Management (IJBSAM), 2011)
Women entrepreneurs face a wide variety of barriers and challenges throughout the life and growth of their entrepreneurial venture. This study expands the knowledge base on women entrepreneurs' needs, specifically their needs in terms of service areas and service delivery method preferences. Twenty three "needed" service areas were identified by 95 Manitoba based women entrepreneurs. The first five included: finding new customers, growth benefits and tools, market expansion, general marketing, and networking skills. This study also examined the differences between urban and rural based entrepreneurs. Two service need areas "how to find mentors and role models" and "legal issues" exhibited statistically significant priority differences. Service delivery methods did not produce any statistically significant differences. Overall, this study concludes that regardless of location, women entrepreneurs' training and support needs are not significantly that different. The effects of entrepreneurial stage and years in business on entrepreneurial support needs are also examined.
Keywords: 650; entrepreneurship; women owned businesses; urban and rural communities; entrepreneurial training; business education; business support services; Canada